Folliculotropic mycosis fungoides: Clinicopathological features: Folikulotropna oblika mycosis fungoides: kliničnopatološke značilnosti - Kovačič, Srečko (Acta Medico-Biotechnica, 2021)
Folliculotropic variant of mycosis fungoides (MF) is a rare type of cutaneous T-cell lymphoma, detected in less than 10% of patients with MF. It occurs mostly in elderly adults, and usually involves the head, neck region, and upper trunk. The diagnosis of this disease is based on a combination of clinical presentation, histology, and T-cell monoclonality. Identification of this variant of disease is important because it may imply worse prognosis and require more intensive treatment.